Parthenolide as Cooperating Agent for Anti-Cancer Treatment of Various Malignancies - Malgorzata Sztiller-Sikorska; Malgorzata Czyz (MDPI AG, 2020)
Primary and acquired resistance of cancer to therapy is often associated with activation of nuclear factor kappa B (NF-κB). Parthenolide (PN) has been shown to inhibit NF-κB signaling and other pro-survival signaling pathways, induce apoptosis and reduce a subpopulation of cancer stem-like cells in several cancers. Multimodal therapies that include PN or its derivatives seem to be promising approaches enhancing sensitivity of cancer cells to therapy and diminishing development of resistance. A number of studies have demonstrated that several drugs with various targets and mechanisms of action can cooperate with PN to eliminate cancer cells or inhibit their proliferation. This review summarizes the current state of knowledge on PN activity and its potential utility as complementary therapy against different cancers.